Chronic Paroxetine Treatment: Effects on Other Non-Serotonergic Neurotransmitter Systems - Ballesteros-Zebadua, Paola; Manjarrez-Marmolejo, Joaquin; Franco-Perez, Javier (CNS & Neurological Disorders - Drug Targets, 2013)
Due to its efficacy and acceptability, paroxetine is situated in the top ten of drugs prescribed for the treatment of major depression and essentially all anxiety disorders. Adults under paroxetine treatment report relief after 4-6 weeks of administration; furthermore, this drug can be prescribed for periods lasting longer than one year. Therefore, paroxetine treatment has a pattern of ingestion that is mainly chronic rather than acute. There is a considerable number of reviews in the literature concerning the effects of paroxetine on the serotonergic system; however, the alterations caused by chronic ingestion of this drug in other neurotransmitter systems have received little attention. For this reason, we consider very important to review the experimental studies concerning the effects of chronic paroxetine intake on neurotransmitter levels, neuronal firing rate and the expression of receptors and transporters in different neurotransmitter systems in the brain. According to the experimental data analyzed in this work, we can establish that long-term paroxetine intake has the ability to increase GABA, glutamate, dopamine and noradrenaline levels in the brain. Furthermore, high levels of AMPA, orexine-1,2 and histamine-1 receptors have been reported in different brain regions after treatment with paroxetine over several weeks. In addition, paroxetine has differential effects on neuropeptide systems, such as galanine, opioid receptors and substance P. Available data lead us to establish that chronic ingestion of paroxetine induces changes in several neurotransmitters and neuropeptides, thus illuminating how each one may contribute to the antidepressant and anxiolytic response elicited by this drug. We consider that all reported changes in the neurotransmitter systems should be further considered to individualize clinical treatment and, in the case of patients taking a drug “cocktail”, to gain better control over drug interactions and adverse effects.
Keywords: neuronal firing rate